Factores de riesgo más frecuentes asociados a la hemorragia digestiva alta en pacientes mayores de 45 años en el hospital general de zona No. 2 - Zarate Mediano, Patricia (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Introduction: High Digestive Hemorrhage (HDA) can be of variceal or non -variceal origin depending on the cause. It has a high incidence in Mexico, it is frequently associated with chronic alcohol or polypharmacy intake. General objective: Determine the most frequent risk factors associated with High digestive bleeding in patients over 45 years. Material and methods: descriptive transverse study, to patient files of both Sexes, hospitalized in the HGZ/MF No.2 by HDA, confirmed by Endoscopy, March From 2017 to May 2022. Descriptive statistics were used for medium quantitative variables and of, for categorical frequencies and percentages. X2 was used to determine association between categorical variables. Significant difference was established with P value <0.05. Results: 104 patient files of both sexes were studied. The hda of non-variceal origin had more frequency, in patients of 66 and 75 years (42.3%). It was determined chronic consumption of NSAIDs and polypharmacy as predominant (83.7% and 85.6%), where the consumption of AAS and Diclofenac were the ones with the highest consumption being in the male sex the one with the highest intake (52.9%); The reason for graduation was for improvement in 97.1%. Conclusions: Chronic NSAIDs and polypharmacy consumption are the factors of most frequent risk associated with high digestive bleeding, being the non -variceal origin The most frequent in the age group from 66 to 75 years, with 97.1% of improvement for improvement.

Introducción: La hemorragia digestiva alta (HDA) puede ser de origen variceal o no variceal dependiendo la causa. Tiene una alta incidencia en México, se encuentra frecuentemente asociada con ingesta crónica de alcohol o polifarmacia. Objetivo general: Determinar los factores de riesgo más frecuentes asociados a la hemorragia digestiva alta en pacientes mayores de 45 años. Material y métodos: Estudio transversal descriptivo, de expedientes de pacientes de ambos sexos, hospitalizados en el HGZ/MF No.2 por HDA, confirmada por endoscopia, de marzo de 2017 a mayo 2022. Se utilizó estadística descriptiva, para variables cuantitativas medias y DE, para categóricas frecuencias y porcentajes. Se utilizó X2 para determinar asociación entre variables categóricas. Se estableció diferencia significativa con p valor < 0.05. Resultados: Se revisaron 104 expedientes de pacientes de ambos sexos. La HDA de origen no variceal tuvo mayor frecuencia, en pacientes de 66 y 75 años (42.3%). Se determinó el consumo crónico de AINES y polifarmacia como predominantes (83.7% y 85.6%), donde el consumo de AAS y diclofenaco fueron los de mayor consumo siendo en el sexo masculino el de mayor ingesta (52.9%); el motivo de egreso fue por mejoría en 97.1%. Conclusiones: El consumo crónico de AINES y la polifarmacia son los factores de riesgo más frecuentes asociados a la hemorragia digestiva alta, siendo la de origen no variceal la más frecuente en el grupo de edad de 66 a 75 años, con un 97.1% de egreso por mejoría.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2025-0081; Hemorragia gastrointestinal; Tracto gastrointestinal superior; Factores de riesgo; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19074